First-line pazopanib in patients with metastatic epithelioid hemangioendothelioma: a retrospective single-center analysis - Anton Burkhard-Meier; Vera Valerie Rechenauer; Vindi Jurinovic; Markus Albertsmeier; Michael Hoberger; Hans Roland Dürr; Alexander Klein; Thomas Knösel; Wolfgang G. Kunz; Andreas Mock; Ada Pusztai; Michael Völkl; et al. (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose Epithelioid hemangioendothelioma (EHE) represents an ultra-rare, translocated vascular sarcoma with a heterogeneous course of disease. The optimal systemic treatment for patients with advanced EHE remains unclear. We sought to evaluate the value of pazopanib (PAZ) as a first-line treatment in metastatic EHE. Methods Thirteen patients with metastatic EHE and PAZ as a first-line treatment at our institution between 2012 und 2023 were reviewed and analyzed with regard to clinical outcomes. Results At a median follow-up of 51.4 months, the median progression-free survival (PFS) and overall survival (OS) were 35.1 and 53.8 months, respectively. In patients with documented prior tumor progression (n = 10), the median PFS and OS were 12.6 and 105 months, respectively. In patients with serosal effusion/ systemic symptoms (n = 4), the median PFS and OS were 6.1 and 10.3 months. The clinical benefit rate of the overall cohort was 62% with no complete or partial responses. Two of four patients experienced a reduction of symptoms (pain and ascites reduction/hemoptysis, respectively) under treatment with PAZ. Toxicity was mainly gastrointestinal and manageable with dose reductions. Permanent treatment interruption due to toxicity was necessary in one patient. Conclusion This is the first study to systematically report survival outcomes for PAZ as a first-line treatment in patients with metastatic EHE. PAZ is active and safe in patients with metastatic EHE and may be considered as an alternative to sirolimus for specific patient subgroups. RECIST criteria should be questioned for evaluation of treatment response in EHE.